Preparation method of aerogel composite thermal insulation material
By preparing reinforced silicon carbide fiber felt and combining it with silicon sol, aerogel modified fiber felt was formed and polyurethane-coated glue was applied, which solved the problem of heavy and limited insulation effect of traditional insulation fabrics, and achieved high-performance thermal insulation, mechanical properties and hydrophobic properties.
Patent Information
- Application Number
- CN202411942339.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional insulation fabrics are thick and have limited insulation effects. The simple aerogel has a fragile texture, poor mechanical properties, and insufficient hydrophobic properties and thermal insulation properties.
Polycarbosilane is used as the precursor to prepare reinforced silicon carbide fiber mats through electrospinning, oxidative crosslinking, high-temperature heat treatment, chemical vapor deposition and other steps, and immerse it in a silicon sol to form an aerogel-modified fiber mat, and finally coat polyurethane-coated glue to improve hydrophobic properties.
The prepared aerogel composite insulation material has excellent thermal insulation performance, excellent mechanical properties and improved hydrophobic properties, effectively ensuring its quality and quality.
Smart Images

Figure BDA0005213995280000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation materials, and in particular to a method for preparing an aerogel composite thermal insulation material. Background Art
[0002] In today's era of pursuing high-quality life and energy conservation and environmental protection, people have put forward higher requirements for the thermal insulation performance of thermal clothing, outdoor equipment, etc. Traditional thermal insulation fabrics mostly rely on thickened cotton layers or ordinary thermal insulation fibers, which are not only thick and heavy, but also have limited thermal insulation effects. Aerogel, as a material with extraordinary thermal insulation properties, brings hope to the development of high-performance thermal insulation fabrics. Aerogel, also known as dry gel, is a form of solid matter. It has types such as gelatin, gum arabic and silica gel. It has a light, crisp, slightly transparent texture, high elasticity and strong adsorption. It can be used in energy storage devices, thermal insulation materials and space probes. The gel removes most of the solvent, so that the liquid content in the gel is much less than the solid content, or the medium filled in the spatial network structure of the gel is gas, and the appearance is solid, forming an aerogel.
[0003] Although aerogel has many advantages mentioned above, the texture of pure aerogel is fragile, and its mechanical properties are not very ideal, so it is difficult to be directly used in fabric production. Furthermore, its hydrophobicity and thermal insulation performance are relatively insufficient, and still need to be further improved. Therefore, the present invention provides a method for preparing an aerogel composite thermal insulation material to solve the above-mentioned technical problems! Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing an aerogel composite thermal insulation material. The prepared aerogel composite thermal insulation material not only has excellent thermal insulation performance, but also has excellent mechanical properties and hydrophobic properties, effectively ensuring its quality.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing an aerogel composite thermal insulation material comprises the following steps:
[0007] Step 1: Using polycarbosilane with a softening point of 200-220° C. as a precursor, dissolving it in a mixed solvent consisting of N,N-dimethylformamide, tetrahydrofuran and xylene to prepare a polycarbosilane solution with a concentration of 0.8-1.2 g / mL, i.e., a spinning solution; then electrospinning the spinning solution, and after oxidative crosslinking and high-temperature heat treatment of the obtained polycarbosilane micro / nano fiber felt, the obtained silicon carbide fiber felt is stored for standby use;
[0008] Step 2: placing the silicon carbide fiber felt obtained in step 1 in a vapor deposition furnace, continuously introducing a gas source, a carrier gas and a dilution gas, and controlling the gas pressure in the furnace to be 700-1200 Pa, and performing chemical vapor deposition at a temperature of 800-1100° C. for 10-20 hours; after the deposition is completed, the furnace temperature is naturally cooled to room temperature, and the obtained reinforced silicon carbide fiber felt is stored and used for standby;
[0009] Step 3, at a temperature of 30-40° C., tetraethoxysilane, ethanol and deionized water are mixed and stirred in a molar ratio of 1:3-5:2-4, and then the pH is adjusted to 2.3-2.8 with a 0.2-0.5 mol / L hydrochloric acid solution; and the pH is adjusted to 6.5-7.5 with a 0.02-0.05 mol / L sodium hydroxide aqueous solution; after mechanical stirring, the obtained silica sol is stored and used for standby;
[0010] Step 4: impregnate the reinforced silicon carbide fiber felt into the silica sol by an infiltration process, so that the silica sol completely immerses the reinforced silicon carbide fiber felt, and then seal it and let it stand at room temperature for 8 to 20 hours to form a gel; the obtained gel is aged at room temperature for 1 to 2 days, and then the solvent is replaced, and then the obtained gel composite is supercritically dried; after drying, the obtained aerogel modified fiber felt is stored and used for standby;
[0011] Step 5: Coat the surface of the aerogel-modified fiber felt obtained in step 4 with a polyurethane coating adhesive, wherein the amount of the polyurethane coating adhesive applied is 20 to 80 g / m 2 After the coating is completed, it is subjected to heat setting treatment, and the final product is the aerogel composite thermal insulation material.
[0012] Furthermore, the mixed solvent is prepared by uniformly mixing N,N-dimethylformamide, tetrahydrofuran and xylene in a volume ratio of 1-3:10:8-12.
[0013] Furthermore, the voltage during the electrospinning process is set to 12-25 kV, the distance between the spinneret and the collector is set to 10-25 cm, and the extrusion speed is set to 0.3-1.5 mL / h.
[0014] Furthermore, the specific steps of the oxidative cross-linking are: placing the polycarbosilane micro / nano fiber felt in a pre-oxidation furnace, raising the furnace temperature to 190-220°C at a rate of 20-30°C / h, and then heat-treating it for 2-5 hours in a hot air atmosphere; after the heat treatment is completed, naturally cool it to room temperature.
[0015] Furthermore, the specific steps of the high-temperature heat treatment are: placing the polycarbosilane micro / nano fiber felt after oxidative cross-linking treatment in a high-temperature furnace, raising the temperature to 1000-1500° C. under the protection of nitrogen, and heat-insulating at this temperature for 1-2 hours.
[0016] Furthermore, in the step 2, the gas source is trichloromethylsilane, the carrier gas is hydrogen, and the dilution gas is argon.
[0017] Furthermore, the specific steps of solvent replacement in step 4 are: the aged gel is added to ethanol and n-hexane in turn for solvent replacement, and the replacement process is kept at a temperature of 40-55°C for 12-15h, and each replacement process is repeated 3-5 times.
[0018] Furthermore, the temperature of the supercritical drying is set at 245-265° C., and ethanol is used for supercritical drying.
[0019] Furthermore, the polyurethane coating adhesive in step five is composed of the following raw materials in parts by weight: 50 to 65 parts of aqueous polyurethane emulsion, 3 to 4 parts of silicone-modified elastic microspheres, 2 to 3 parts of antistatic agent, 0.5 to 0.8 parts of ultraviolet absorber, 0.2 to 0.4 parts of BYK-019 aqueous defoamer, 2 to 3 parts of thickener and 25 to 35 parts of deionized water.
[0020] Furthermore, the ultraviolet absorber is selected from any one of 2-(2-hydroxy-5-methylphenyl)-benzotriazole, 2-(2-hydroxy-3,5-tert-butylphenyl)-5-chlorobenzotriazole, and 2-(2-hydroxy-3,5-di-tert-amylphenyl)-benzotriazole.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention uses polycarbosilane as a precursor, dissolves it in a mixed solvent to prepare a polycarbosilane solution, i.e., a spinning solution. Then, the spinning solution is subjected to electrostatic spinning, and the obtained polycarbosilane micro / nano fiber felt is successively subjected to oxidative crosslinking and high-temperature heat treatment to obtain a silicon carbide fiber felt. Then, the silicon carbide fiber felt is placed in a vapor deposition furnace, and chemical vapor deposition is performed using trichloromethylsilane as a gas source, hydrogen as a carrier gas, and argon as a diluent gas, and finally a relatively dense layer of small-particle silicon carbide is deposited on the surface of the silicon carbide fiber felt, thereby strengthening the silicon carbide fiber felt, i.e., a strengthened silicon carbide fiber felt is obtained. The strengthened silicon carbide fiber felt is immersed in silica sol, and an aerogel-modified fiber felt is obtained after aging, solvent replacement, and supercritical drying. Under the synergistic cooperation of silica aerogel, silicon carbide fiber felt, and small-particle silicon carbide, the prepared aerogel-modified fiber felt not only has excellent thermal insulation and warmth retention properties, but also has excellent mechanical properties. In addition, by coating the surface of the aerogel modified fiber felt with polyurethane coating glue, its hydrophobic properties are effectively improved, so that the finally prepared aerogel composite insulation material not only has excellent thermal insulation properties, but also has excellent mechanical properties and hydrophobic properties, effectively ensuring its quality. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1
[0025] A method for preparing an aerogel composite thermal insulation material comprises the following steps:
[0026] Step 1: Using polycarbosilane with a softening point of 200° C. as a precursor, dissolving it in a mixed solvent consisting of N,N-dimethylformamide, tetrahydrofuran and xylene to prepare a polycarbosilane solution with a concentration of 0.8 g / mL, i.e., a spinning solution; then electrospinning the spinning solution, and after oxidative crosslinking and high-temperature heat treatment of the obtained polycarbosilane micro / nano fiber felt, the obtained silicon carbide fiber felt is stored for standby use;
[0027] The mixed solvent is prepared by uniformly mixing N,N-dimethylformamide, tetrahydrofuran and xylene in a volume ratio of 1:10:8;
[0028] The voltage during electrospinning was set to 12 kV, the distance between the spinneret and the collector was set to 10 cm, and the extrusion rate was set to 0.3 mL / h;
[0029] The specific steps of oxidative cross-linking are: placing the polycarbosilane micro / nano fiber felt in a pre-oxidation furnace, raising the furnace temperature to 190°C at a rate of 20°C / h, and then heat-treating it for 5 hours in a hot air atmosphere; after the heat treatment is completed, naturally cooling it to room temperature;
[0030] The specific steps of high temperature heat treatment are: placing the polycarbosilane micro / nano fiber felt after oxidation cross-linking treatment in a high temperature furnace, raising the temperature to 1000° C. under the protection of nitrogen, and heat-insulating treatment at this temperature for 2 hours;
[0031] Step 2: placing the silicon carbide fiber felt obtained in step 1 in a vapor deposition furnace, continuously introducing trichloromethylsilane, hydrogen and argon, and controlling the pressure in the furnace to 700 Pa, and performing chemical vapor deposition at a temperature of 800° C. for 10 hours; after the deposition is completed, the furnace temperature is naturally cooled to room temperature, and the obtained reinforced silicon carbide fiber felt is stored and used for standby;
[0032] Step 3, at a temperature of 30°C, tetraethoxysilane, ethanol and deionized water are mixed and stirred in a molar ratio of 1:3:2, and then the pH is adjusted to 2.3 with a 0.2 mol / L hydrochloric acid solution; and the pH is adjusted to 6.5 with a 0.02 mol / L sodium hydroxide aqueous solution; after mechanical stirring, the obtained silica sol is stored and used for standby;
[0033] Step 4: impregnate the reinforced silicon carbide fiber felt into the silica sol by an infiltration process, so that the silica sol completely immerses the reinforced silicon carbide fiber felt, and then seal it and let it stand at room temperature for 8 hours to form a gel; the obtained gel is aged at room temperature for 1 day and then the solvent is replaced, and then the obtained gel composite is supercritically dried; after drying, the obtained aerogel modified fiber felt is stored and used for standby;
[0034] The specific steps of solvent replacement are as follows: the aged gel is added to ethanol and n-hexane in turn for solvent replacement, and the replacement process is kept at 40°C for 15 hours, and each replacement process is repeated 3 times; the temperature of supercritical drying is set to 245°C, and ethanol is used for supercritical drying;
[0035] Step 5: Coat the surface of the aerogel-modified fiber felt obtained in step 4 with a polyurethane coating adhesive, wherein the amount of the polyurethane coating adhesive applied is 20 g / m 2 After the coating is completed, it is subjected to heat setting treatment, and the final product is the finished aerogel composite thermal insulation material;
[0036] The polyurethane coating adhesive is composed of the following raw materials in parts by weight: 50 parts of water-based polyurethane emulsion, 3 parts of silicone-modified elastic microspheres, 2 parts of antistatic agent, 0.5 parts of 2-(2-hydroxy-5-methylphenyl)-benzotriazole, 0.2 parts of BYK-019 water-based defoamer, 2 parts of thickener and 25 parts of deionized water;
[0037] Among them, the water-based polyurethane emulsion uses FS-5707, a product of Liaoning Hengxing Fine Chemical Co., Ltd.;
[0038] The silicone-modified elastic microspheres are F-77D, a product of Beijing Senchang Taihe Technology Co., Ltd.;
[0039] The antistatic agent is FSK-9 produced by Liaoning Hengxing Fine Chemical Co., Ltd.
[0040] The thickener is an associative water-based polyurethane thickener, specifically SN-612 produced by Guangzhou Runhong Chemical Co., Ltd.
[0041] Example 2
[0042] A method for preparing an aerogel composite thermal insulation material comprises the following steps:
[0043] Step 1: using polycarbosilane with a softening point of 220°C as a precursor, dissolving it in a mixed solvent consisting of N,N-dimethylformamide, tetrahydrofuran and xylene to prepare a polycarbosilane solution with a concentration of 1 g / mL, i.e., a spinning solution; then electrospinning the spinning solution, and after oxidative crosslinking and high-temperature heat treatment of the obtained polycarbosilane micro / nano fiber felt, the obtained silicon carbide fiber felt is stored for standby use;
[0044] The mixed solvent is prepared by uniformly mixing N,N-dimethylformamide, tetrahydrofuran and xylene in a volume ratio of 2:10:10;
[0045] The voltage during electrospinning was set to 20 kV, the distance between the spinneret and the collector was set to 15 cm, and the extrusion rate was set to 0.8 mL / h;
[0046] The specific steps of oxidative cross-linking are: placing the polycarbosilane micro / nano fiber felt in a pre-oxidation furnace, raising the furnace temperature to 200°C at a rate of 25°C / h, and then heat-treating it for 3 hours in a hot air atmosphere; after the heat treatment is completed, naturally cooling it to room temperature;
[0047] The specific steps of high temperature heat treatment are: placing the polycarbosilane micro / nano fiber felt after oxidation cross-linking treatment in a high temperature furnace, raising the temperature to 1200° C. under the protection of nitrogen, and heat-insulating treatment at this temperature for 2 hours;
[0048] Step 2: placing the silicon carbide fiber felt obtained in step 1 in a vapor deposition furnace, continuously introducing trichloromethylsilane, hydrogen and argon, and controlling the pressure in the furnace to be 1000 Pa, and performing chemical vapor deposition at a temperature of 1000° C. for 15 hours; after the deposition is completed, the furnace temperature is naturally cooled to room temperature, and the obtained reinforced silicon carbide fiber felt is stored and used for standby;
[0049] Step 3, at a temperature of 35°C, tetraethoxysilane, ethanol and deionized water are mixed and stirred in a molar ratio of 1:4:3, and then the pH is adjusted to 2.5 with a 0.3 mol / L hydrochloric acid solution; and the pH is adjusted to 7 with a 0.03 mol / L sodium hydroxide aqueous solution; after mechanical stirring, the obtained silica sol is stored and used for standby;
[0050] Step 4: impregnate the reinforced silicon carbide fiber felt into the silica sol by an infiltration process, so that the silica sol completely immerses the reinforced silicon carbide fiber felt, and then seal it and let it stand at room temperature for 15 hours to form a gel; the obtained gel is aged at room temperature for 2 days, and then the solvent is replaced, and then the obtained gel composite is supercritically dried; after drying, the obtained aerogel modified fiber felt is stored and used for standby;
[0051] The specific steps of solvent replacement are as follows: the aged gel is added to ethanol and n-hexane for solvent replacement in sequence, and the replacement process is kept at 50°C for 14 hours, and each replacement process is repeated 4 times; the temperature of supercritical drying is set to 255°C, and ethanol is used for supercritical drying;
[0052] Step 5: Coat the surface of the aerogel-modified fiber felt obtained in step 4 with a polyurethane coating adhesive, wherein the amount of the polyurethane coating adhesive applied is 50 g / m 2 After the coating is completed, it is subjected to heat setting treatment, and the final product is the finished aerogel composite thermal insulation material;
[0053] The polyurethane coating adhesive is composed of the following raw materials in parts by weight: 60 parts of aqueous polyurethane emulsion, 4 parts of silicone modified elastic microspheres, 3 parts of antistatic agent, 0.6 parts of 2-(2-hydroxy-3,5-tert-butylphenyl)-5-chlorobenzotriazole, 0.3 parts of BYK-019 aqueous defoaming agent, 3 parts of thickener and 30 parts of deionized water.
[0054] Example 3
[0055] A method for preparing an aerogel composite thermal insulation material comprises the following steps:
[0056] Step 1: Using polycarbosilane with a softening point of 220° C. as a precursor, dissolving it in a mixed solvent consisting of N,N-dimethylformamide, tetrahydrofuran and xylene to prepare a polycarbosilane solution with a concentration of 1.2 g / mL, i.e., a spinning solution; then electrospinning the spinning solution, and after oxidative crosslinking and high-temperature heat treatment of the obtained polycarbosilane micro / nano fiber felt, the obtained silicon carbide fiber felt is stored for standby use;
[0057] The mixed solvent is prepared by uniformly mixing N,N-dimethylformamide, tetrahydrofuran and xylene in a volume ratio of 3:10:12;
[0058] The voltage during electrospinning was set to 25 kV, the distance between the spinneret and the collector was set to 25 cm, and the extrusion rate was set to 1.5 mL / h;
[0059] The specific steps of oxidative cross-linking are as follows: placing the polycarbosilane micro / nano fiber felt in a pre-oxidation furnace, raising the furnace temperature to 220°C at a rate of 30°C / h, and then heat-treating it for 2 hours in a hot air atmosphere; after the heat treatment is completed, naturally cooling it to room temperature;
[0060] The specific steps of high temperature heat treatment are: placing the polycarbosilane micro / nano fiber felt after oxidation cross-linking treatment in a high temperature furnace, raising the temperature to 1500° C. under the protection of nitrogen, and heat-treating at this temperature for 1 hour;
[0061] Step 2: placing the silicon carbide fiber felt obtained in step 1 in a vapor deposition furnace, continuously introducing trichloromethylsilane, hydrogen and argon, and controlling the pressure in the furnace to be 1200 Pa, and performing chemical vapor deposition at a temperature of 1100° C. for 20 hours; after the deposition is completed, the furnace temperature is naturally cooled to room temperature, and the obtained reinforced silicon carbide fiber felt is stored and used for standby;
[0062] Step 3, at a temperature of 40°C, tetraethoxysilane, ethanol and deionized water are mixed and stirred in a molar ratio of 1:5:4, and then the pH is adjusted to 2.8 with a 0.5 mol / L hydrochloric acid solution; and the pH is adjusted to 7.5 with a 0.05 mol / L sodium hydroxide aqueous solution; after mechanical stirring, the obtained silica sol is stored and used for standby;
[0063] Step 4: impregnate the reinforced silicon carbide fiber felt into the silica sol by an infiltration process, so that the silica sol completely immerses the reinforced silicon carbide fiber felt, and then seal it and let it stand at room temperature for 20 hours to form a gel; the obtained gel is aged at room temperature for 2 days, and then the solvent is replaced, and then the obtained gel composite is supercritically dried; after drying, the obtained aerogel modified fiber felt is stored and used for standby;
[0064] The specific steps of solvent replacement are as follows: the aged gel is added to ethanol and n-hexane in turn for solvent replacement, and the replacement process is kept at 55°C for 15 hours, and each replacement process is repeated 5 times; the temperature of supercritical drying is set to 265°C, and ethanol is used for supercritical drying;
[0065] Step 5: Coat the surface of the aerogel-modified fiber felt obtained in step 4 with a polyurethane coating adhesive, wherein the amount of the polyurethane coating adhesive applied is 80 g / m 2 After the coating is completed, it is subjected to heat setting treatment, and the final product is the finished aerogel composite thermal insulation material;
[0066] The polyurethane coating adhesive is composed of the following raw materials in parts by weight: 65 parts of aqueous polyurethane emulsion, 4 parts of silicone modified elastic microspheres, 3 parts of antistatic agent, 0.8 parts of 2-(2-hydroxy-3,5-di-tert-amylphenyl)-benzotriazole, 0.4 parts of BYK-019 aqueous defoaming agent, 3 parts of thickener and 35 parts of deionized water.
[0067] Performance Testing
[0068] The relevant properties of the aerogel composite thermal insulation material samples provided in Examples 1 to 3 were tested respectively, and the obtained test data were recorded in the following table:
[0069]
[0070] By comparing and analyzing the relevant data in the table, it can be seen that the prepared aerogel composite thermal insulation material not only has excellent thermal insulation performance, but also has excellent mechanical properties and hydrophobic properties, which effectively guarantees its quality. This shows that the aerogel composite thermal insulation material and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.
[0071] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0072] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for preparing an aerogel composite thermal insulation material, characterized in that: The following steps are involved: Step 1: Using polycarbosilane with a softening point of 200-220° C. as a precursor, dissolving it in a mixed solvent consisting of N,N-dimethylformamide, tetrahydrofuran and xylene to prepare a polycarbosilane solution with a concentration of 0.8-1.2 g / mL, i.e., a spinning solution; then electrospinning the spinning solution, and after oxidative crosslinking and high-temperature heat treatment of the obtained polycarbosilane micro / nano fiber felt, the obtained silicon carbide fiber felt is stored for standby use; Step 2: placing the silicon carbide fiber felt obtained in step 1 in a vapor deposition furnace, continuously introducing a gas source, a carrier gas and a dilution gas, and controlling the gas pressure in the furnace to be 700-1200 Pa, and performing chemical vapor deposition at a temperature of 800-1100° C. for 10-20 hours; after the deposition is completed, the furnace temperature is naturally cooled to room temperature, and the obtained reinforced silicon carbide fiber felt is stored and used for standby; Step 3, at a temperature of 30-40° C., tetraethoxysilane, ethanol and deionized water are mixed and stirred in a molar ratio of 1:3-5:2-4, and then the pH is adjusted to 2.3-2.8 with a 0.2-0.5 mol / L hydrochloric acid solution; and the pH is adjusted to 6.5-7.5 with a 0.02-0.05 mol / L sodium hydroxide aqueous solution; after mechanical stirring, the obtained silica sol is stored and used for standby; Step 4: impregnate the reinforced silicon carbide fiber felt into the silica sol by an infiltration process, so that the silica sol completely immerses the reinforced silicon carbide fiber felt, and then seal it and let it stand at room temperature for 8 to 20 hours to form a gel; the obtained gel is aged at room temperature for 1 to 2 days, and then the solvent is replaced, and then the obtained gel composite is supercritically dried; after drying, the obtained aerogel modified fiber felt is stored and used for standby; Step 5: Coat the surface of the aerogel-modified fiber felt obtained in step 4 with a polyurethane coating adhesive, wherein the amount of the polyurethane coating adhesive applied is 20 to 80 g / m 2 After the coating is completed, it is subjected to heat setting treatment, and the final product is the aerogel composite thermal insulation material.
2. The method for preparing an aerogel composite thermal insulation material according to claim 1, characterized in that: The mixed solvent is prepared by uniformly mixing N,N-dimethylformamide, tetrahydrofuran and xylene in a volume ratio of 1-3:10:8-12.
3. The method for preparing an aerogel composite thermal insulation material according to claim 1, characterized in that: The voltage during the electrospinning process is set to 12-25 kV, the distance between the spinneret and the collector is set to 10-25 cm, and the extrusion speed is set to 0.3-1.5 mL / h.
4. The method for preparing an aerogel composite thermal insulation material according to claim 1, characterized in that: The specific steps of the oxidative crosslinking are: placing the polycarbosilane micro / nano fiber felt in a pre-oxidation furnace, raising the furnace temperature to 190-220°C at a rate of 20-30°C / h, and then heat-treating it for 2-5 hours in a hot air atmosphere; after the heat treatment is completed, naturally cooling it to room temperature.
5. The method for preparing an aerogel composite thermal insulation material according to claim 1, characterized in that: The specific steps of the high-temperature heat treatment are: placing the polycarbosilane micro / nano fiber felt after oxidative cross-linking treatment in a high-temperature furnace, raising the temperature to 1000-1500° C. under the protection of nitrogen, and heat-insulating the felt at this temperature for 1-2 hours.
6. The method for preparing an aerogel composite thermal insulation material according to claim 1, characterized in that: The gas source in step 2 is trichloromethylsilane, the carrier gas is hydrogen, and the diluent gas is argon.
7. The method for preparing an aerogel composite thermal insulation material according to claim 1, characterized in that: The specific steps of solvent replacement in step 4 are: adding the aged gel to ethanol and n-hexane in turn for solvent replacement, and keeping the temperature at 40-55°C for 12-15h during the replacement process, and repeating each replacement process 3-5 times.
8. The method for preparing an aerogel composite thermal insulation material according to claim 1, characterized in that: The temperature of the supercritical drying is set at 245-265° C., and ethanol is used for supercritical drying.
9. The method for preparing an aerogel composite thermal insulation material according to claim 1, characterized in that: The polyurethane coating adhesive in step five is composed of the following raw materials in parts by weight: 50 to 65 parts of aqueous polyurethane emulsion, 3 to 4 parts of silicone-modified elastic microspheres, 2 to 3 parts of antistatic agent, 0.5 to 0.8 parts of ultraviolet absorber, 0.2 to 0.4 parts of BYK-019 aqueous defoamer, 2 to 3 parts of thickener and 25 to 35 parts of deionized water.
10. The method for preparing an aerogel composite thermal insulation material according to claim 9, characterized in that: The ultraviolet absorber is selected from any one of 2-(2-hydroxy-5-methylphenyl)-benzotriazole, 2-(2-hydroxy-3,5-tert-butylphenyl)-5-chlorobenzotriazole, and 2-(2-hydroxy-3,5-di-tert-pentylphenyl)-benzotriazole.